PENGARUH STRATEGI PEMBELAJARAN DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR MATEMATIKA - Rosliana Siregar (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2012)
This research aim to know of difference between result learn the studentmathematics taught by using strategy of study cooperative type STAD and result oflearning student mathematics by using strategy of study ekspositori. The  method isquasi experiment. This research is executed SMP Negeri 11 Medan. Instrumentused together the data  test result of learning and enquette motivate to haveachievement. Technique analysis the data used by ANAVA 2x2. The result analysisof research indicate that result learn the student mathematics taught by usingstrategy study of higher type STAD cooperative than result learn the studentmathematics taught by using strategy of study ekspositori (Fcalculate = 4,698 >Ftabel = 3,96;  there are difference which signifikan of result learn the studentmathematics having high achievement motivation with the student having lowmotivation achievement, (Fcalculate = 27,9 > Ftabel = 3,96), and there areinteraction between study strategy and motivate to have achievement in influencingresult learn the student mathematics (Fcalculate = 12,45 > Ftabel = 3,96). Result ofinferential research that strategy study of better type STAD cooperative taught tostudent having motivation  have high achievement and good study ekspositoristrategy used to student having motivation  have low achievement and there areinteraction of study strategy and motivate the to have achievement.